Effect of mining parameters on surface deformation and coal pillar stability under customized shortwall mining of deep extra-thick coal seams. (November 2021) - Jiang, Shuyin; Fan, Gangwei; Li, Qizhen; Zhang, Shizhong; Chen, Liang
Abstract: Underestimation of customized shortwall mining parameters of deep extra-thick coal seams (namely, mining height, mining width, and pillar width) may result in coal pillar instability, surface subsidence, and mining structure failure, while their overestimation would cause a waste of coal resources. This study proposes a new method for optimizing these parameters, whose main purpose is to achieve the maximum coal recovery rate while satisfying surface deformation and coal pillar stability requirements. A case study of an extra-thick coal seam in Eastern China with one km-overburden depth and a thickness of 10 m was analyzed. First, a new method for predicting surface deformation under deep customized shortwall mining based on surface deformation data from fully caving mining was proposed. The variation pattern of the extreme values of surface deformation parameters (including surface subsidence, tilt, curvature, and horizontal strain) versus the area-based recovery rate and mining width was analyzed. After that, the evolution law of the surface deformation with the changing mining height and area-based recovery rate was simulated using the FLAC3D software. The maximum recovery rate and the corresponding mining height, the area-based recovery rate were preliminarily determined, while the surface deformation fell within the allowable range. Simulations of evolutions of the plastic zone width, elastic core ratio, and vertical stress of coal pillars with varying coal pillar width under the maximum recovery rate were performed. The optimal mining scheme had a mining height of 10, a mining width of 100, a coal pillar width of 122 m. It ensured the coal pillar's long-term stability with the surface deformation within the allowable range and achieved the maximum coal recovery rate of 45%. These findings are considered instrumental in the customized shortwall mining of extra-thick coal seams under buildings, in particular, under Eastern China mining and geological conditions. Highlights: The mining height is considered in the designing of customized shortwall mining parameters. A new method for predicting surface deformation under deep customized shortwall mining was proposed. The surface deformation slightly dropped with the mining width reduction under a 1 km-burial depth. The greater the mining width, the better the stability of the coal pillar. An innovative method for optimizing customized shortwall mining parameters was proposed.